Knowledge transfer of higher education in México (Revista cientifica In Vestigium Ire, 2020)
The incubation of enterprises from public higher education institutions (HEIs) in Mexico is a recurring theme in the discourses, however, the articulation of this technology transfer is incipient, because only a minimum percentage of these have models of business incubators and only a few have institutional policies for this purpose. Thus, the objective of this research was to analyze the characteristics of technology transfer (TC) in higher education in Mexico, based on: entrepreneurial culture, business incubator model, public policies for technology transfer (TT) and institutional policies for TT. The methodology was documentary, extracted from a sample of 187 HEI belonging to the National Association of Universities and Higher Education Institutions (ANUIES) of Mexico. The hypothesis proposed is that in the HEIs of Mexico, technology transfer activities are carried out, but there are no written policies established on this subject. The results show the incipient technology transfer in Mexico; although the entrepreneurial culture is promoted in the HEIs of the country, only a minimum percentage of them have business incubator models and only a few have established and documented institutional policies.
Keywords: Knowledge transfer; technology transfer service; technology dissemination; entrepreneur